2021
DOI: 10.46300/9106.2021.15.137
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Fuzzy-ISM, Fuzzy-AHP, and Fuzzy-MICMAC Approach under Trapezoid Fuzzy Linguistic to Analyze Enablers of The Logistics Outsourcing Relationship: Mekong Delta, Vietnam Rice Supply Chain Context

Abstract: The purpose of this paper is to analyze the effects of the factors and determine the importance of these factors to the LO relationship with the desire to improve the efficiency in logistics activities of the supply chain. An integrated approach including Fuzzy Interpretation Structure Model (FISM), Fuzzy Cross-Impact Matrix Multiplication Applied to Classification (FMICMAC) analysis, Fuzzy Analytic Hierarchy Process (FAHP) is structured in reaching this purpose. Specifically, the impact of factors on the LO r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…The reasons for using the AHP method [7] for risk measurement in the paper are as follows: (1) AHP is a scientific method combining qualitative and quantitative methods, which is suitable for some evaluation and trade-offs without structural characteristics; (2) The structure of AHP method is highly similar to the hierarchical model structure of military logistics outsourcing risk;…”
Section: Risk Measurement Based On Ahpmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for using the AHP method [7] for risk measurement in the paper are as follows: (1) AHP is a scientific method combining qualitative and quantitative methods, which is suitable for some evaluation and trade-offs without structural characteristics; (2) The structure of AHP method is highly similar to the hierarchical model structure of military logistics outsourcing risk;…”
Section: Risk Measurement Based On Ahpmentioning
confidence: 99%
“…Many studies are biased towards qualitative research. A few scholars have summarized the quantitative evaluation methods of military logistics outsourcing risk, such as the fuzzy comprehensive evaluation method [1], analytic hierarchy process (AHP) [7], structural entropy weight method [8], etc; However, from the perspective of risk influencing factors, on the one hand, the analysis is not comprehensive and reasonable, such as outsourcing subject risk, outsourcing object risk, outsourcing environment risk, etc. [2] but does not include others; on the other hand, the existing research is not detailed enough, and there are few specific, practical and quantitative studies.…”
Section: Introductionmentioning
confidence: 99%
“…Liu and Li [16] used blockchain technology in the supply chain and suggested that blockchain technology can improve the efficiency of the supply chain while securing the reliability of information to correct abnormal data in the supply chain. Loi et al [17] used an integrated approach including a fuzzy interpretation structure model (FISM), fuzzy cross-impact matrix multiplication applied to classification (FMICMAC) analysis, and fuzzy analytic hierarchy process (FAHP) to the rice supply chain and explained that the logistics activities of the supply chain are improved through their use. Sakai [18] proposed an integrated human management system for the strategic operation of global production to realize "simultaneous start-up and same quality" around the world and proved its efficiency by applying it in the field.…”
Section: Introductionmentioning
confidence: 99%